Arabic Grammatical And Lexical Cohesion Tools In Ramadhan Al-Buti’s Friday Khutbah/ آليات الاتّساق النحويّ والمعجميّ في خطبة الجمعة لرمضان البوطي - Musling, Mohd Nizwan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The linguistic aspect is one of the essential components of the Khutbah, significantly impacting the text's formation as a coherent structure that contributes to persuasion and influence. However, it depends on fulfilling textual criteria, including syntactical and lexical cohesion. Thus, the research aims to examine the availability of linguistic cohesion tools in the Friday Khutbah text by Muhammad Said Ramadhan Al-Buti, with an indication of its function at the level of interdependence and correlation between the components of the Khutbah grammatically and lexically. The research utilizes the descriptive analytical method in reaching its primary objective by investing the textual linguistics or grammar in the light of the cohesion criteria that take the characteristic of consistency and continuity in the Khutbah. One of the study's most important findings is that the Khutbah was characterised by employing two main tools of grammatical cohesions, namely reference: indicative and conscientious, and linking with various forms: additional, affective, reversal, and causal. The tools of lexical cohesion in the Khutbah are represented in repetition (complete, partial, and parallel) and the link with the relationship of correspondence and antagonism, similarity, synonymy, and complementarity. These cohesion tools perform five functions: formation of the Khutbah and the connection between its parts, linguistic economy, confirmation of the meaning of a single idea, clarification and elaboration of the focus of the Khutbah, and expansion by integrating several ideas into one theme. Considering this, the preparation of the Friday Khutbah should consider these cohesion tools with other textuality criteria to ensure the success of the message delivered to its recipient.